The New Eco-Schemes: Navigating a Narrow Fairway; Les nouveaux écorégimes : naviguer sur un chenal étroit; Die neuen Eco-Schemes: Navigieren im schmalen Fahrwasser - Uwe Latacz-Lohmann; Mette Termansen; Chi Nguyen (EuroChoices, 2022)
This article highlights some key challenges and trade-offs with which national policy designers have to contend in devising national eco-schemes for agriculture. We show that policy designers operate in a narrow design space which is constrained by various political and legal requirements. One key challenge is to design a reward system that allows the uptake of eco-schemes by farmers to be aligned with a given budget. We present four broad implementation models for eco-schemes and discuss their merits and shortcomings in light of stipulated requirements. These are the 'greening model', the 'modified greening model', the 'eco-points model' and the 'AECS model' in the style of the agri-environmental and climate schemes of CAP Pillar 2. We conclude that the eco-points model is likely to be the most suitable. By stipulating that individual farmers must reach a certain minimum number of points per hectare (eligibility threshold), but are not entitled to payments for points that exceed a certain upper limit per hectare (cut-off), it allows demand from farmers for inclusion in a scheme to be steered such that aggregate uptake coincides with the budget; thereby reducing the risk of over- or under-subscription while maintaining flexibility to cater for heterogeneity in site conditions.
Keywords: 630